Implementation of Blended Learning to Improve Student's Social and Academic Skills - Fandi Suhandi; Umar Umar; Roni Hartono (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The use of blended learning methods can improve learning outcomes and learning effectiveness of students in Civics subjects at SMA Negeri 1 Sumbawa Besar. The purpose of this study was to determine the application of the Blended Learning model to improving social and academic skills and learning effectiveness of students at SMA Negeri 1 Sumbawa Besar. The sampling technique used in this research is purposive sampling. The data analysis technique used is descriptive and statistical analysis. This research uses Mix Methods research with an experimental approach. The number of samples used in this study were 74 samples where each sample was given the same treatment by observing, interviewing and documenting learning outcomes so as to achieve results above the minimum completeness criteria and there was a significant increase between the PTS mean value is 83.86 with minimum value 74 and the maximum value is 96 and the PASmean value is 88.73 with minimum value 76 and maximum value is 100.Based on the results of these studies, it can be proven that learning in Civics subjects using the blended learning method can improve the learning outcomes of SMA Negeri 1 Sumbawa Besar students which is indicated by the increase in the value of social skills and academic skills, besides the learning process using the blended learning method can actually increase the effectiveness of learning at SMA Negeri 1 Sumbawa Besar.